2012
DOI: 10.1017/s1466046612000026
|View full text |Cite
|
Sign up to set email alerts
|

Research Article: Three Tools for Evaluating Participation: Focus Groups, Q Method, and Surveys

Abstract: To enable successful public participation in environmental decision making, practitioners need to know what works, but evaluation of proposed and existing processes is often lacking. We tested three tools for evaluation-focus groups, Q method, and surveys-at two contaminated sites with extensive public participation. Each tool is evaluated based on its requirements for implementation, the information it produces, and its acceptability to stakeholders. Which tool is most appropriate depends heavily on the avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Completed over a three-month period in late 2015 and early 2016, the study compares capabilities variables related to household characteristicssuch as education, age, access to finance, and membership in an intermediary NGO or community organizationto assess factors correlated with adoption of DRWH. Questionnaire surveys, focus groups and direct observations were all used to collect primary data as part of an integrated approach to data collection and triangulation (Cresswell, 2002;Danielson, Tuler, Santos, Webler, & Chess, 2012;Flick, 2014). The districts chosen for study are shown in Figure 3, and basic socio-economic data for these districts are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Completed over a three-month period in late 2015 and early 2016, the study compares capabilities variables related to household characteristicssuch as education, age, access to finance, and membership in an intermediary NGO or community organizationto assess factors correlated with adoption of DRWH. Questionnaire surveys, focus groups and direct observations were all used to collect primary data as part of an integrated approach to data collection and triangulation (Cresswell, 2002;Danielson, Tuler, Santos, Webler, & Chess, 2012;Flick, 2014). The districts chosen for study are shown in Figure 3, and basic socio-economic data for these districts are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…An initial, NGO-facing, focus group was organized by the Uganda Rainwater Harvesting Association during a two-day public dialogue in Gulu, northern Uganda, attended by 12 representatives of local government and NGOs. As Danielson et al (2012) point out, focus groups are a kind of group interview that capitalizes on communication between research participants in order to generate data. This means that instead of the researcher asking each person to respond to a question in turn, people are encouraged to talk to one another, with the researcher noting areas of concord and discord.…”
Section: Methodsmentioning
confidence: 99%
“…Given that no systematic research has been published on adherence to CAP guidelines, we needed a qualitative research method to explore hidden reasons for (non)adherence. Focus groups fit the purpose of our study best, as this method provides the best opportunity for developing an in-depth understanding of people's viewpoints [47].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“… 3. It should also be noted that there are various methodologies that exist to evaluate public participation that vary in time spent in preparation, cost, technical proficiency, depth and quality of information, etc. (Chess, 2000; Danielson et al, 2012). Choosing effective tools for evaluations are as important as choosing good criteria for evaluation, though this would of course be further complicated on a global scale. …”
mentioning
confidence: 99%